Administrative, financial, criminal-legal and theoretical-metodological aspects of regulating social relations in government bodies - Halunko, Vira Mykolaivna; Maksimentseva, Nadiia Oleksandrivna; Poltoratskyi, Oleksandr Oleksandrovych; Maksimentsev, Maksym Henadiiovych; Tsareva, Iryna Valeriivna (Maracaibo: Universidad del Zulia. Instituto de Estudios Políticos y Derecho Público, 2023)
The purpose of the research was to define the theoretical, administrative and civil law aspects of the regulation of social relations. Consequently, the article specifies the means of social regulation, which include components of legal, moral, corporate and customary, etc. type. It has been shown that legal regulation of social relations is defined as an intentional action on the behavior of people and social relations with the help of legal (juridical) means. The methodological basis of the research is presented as comparative-legal and systematic analysis, formal-legal method, method of interpretation, hermeneutic method, as well as methods of analysis and synthesis. By way of conclusion it has been proved that since the object of legal regulation is presented as social relations, legal regulation is determined by some objective and subjective factors. As contributions, the following factors of social relations have been determined: level of economic development of society; social structure of society; level of maturity and stability of social relations; level of legal culture of citizens; level of certainty of the subject of social relations, means and methods of legal regulation.

El objeto de la investigación fue defnir los aspectos teóricos, administrativos y de derecho civil de la regulación de las relaciones sociales. En consecuencia, el artículo precisa los medios de regulación social, que incluyen componentes de tipo: legal, moral, corporativa y de costumbres, etc. Se ha demostrado que la regulación legal de las relaciones sociales es defnida como una acción intencional sobre el comportamiento de las personas y las relaciones sociales con la ayuda de medios legales (jurídicos). La base metodológica de la investigación se presenta como análisis comparativo-legal y sistemático, método formal-legal, método de interpretación, método hermenéutico, así como métodos de análisis y síntesis. A modo de conclusión se ha probado que, dado que el objeto de la regulación jurídica se presenta como las relaciones sociales, la regulación jurídica está determinada por algunos factores objetivos y subjetivos. Como aportes, se han determinado los siguientes factores de las relaciones sociales: nivel de desarrollo económico de la sociedad; estructura social de la sociedad; nivel de madurez y estabilidad de las relaciones sociales; nivel de cultura jurídica de los ciudadanos; nivel de certeza del tema de las relaciones sociales, medios y métodos de regulación legal.
Aspectos administrativos, fnancieros, penal-jurídicos y teórico-metodológicos de la regulación de las relaciones sociales en los órganos de gobierno
Keywords: social relations; legal regulation; state model; legal phenomena; legal norms; суспільні відносини; правове регулювання; модель держави; правові явища; правові норми; relaciones sociales; regulación jurídica; modelo de Estado; fenómenos jurídicos; normas jurídicas